Determination of mean sea level rise in Peninsular Malaysia - 387611 Chuang, Kuang Hong (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005